Adipose‐derived mesenchymal stem cells stereotactic transplantation alleviate brain edema from intracerebral hemorrhage. Issue 9 (8th April 2019) - Zhang, Ye; Deng, Hong; Hu, Yang; Pan, Chao; Wu, Guofeng; Li, Qi; Tang, Zhouping
Abstract: Adipose‐derived mesenchymal stromal cells (ADSCs) exhibited high potential in tissue repair and regeneration, and it has been proved that ADSCs could protect brain cells from apoptosis and maintaining blood‐brain barrier stability after cerebral vascular disease. In this study, we evaluated the therapeutic potential and mechanism of ADSCs stereotactic transplantation in intracerebral hemorrhage (ICH) mice model and hemin‐treated astrocytes. Mice were divided into three groups: sham group, ICH + PBS group, and ICH + ADSC group. Mice in ICH + ADSC group received ADSCs cell suspension stereotactic transplantation into the area beside the bleeding region. Astrocytes were divided into three groups: control group, hemin group, and hemin + ADSC group. Astrocytes in hemin + ADSC group were cultured in ADSCs‐astrocyte no‐contact coculture system and treated with 30 μM hemin solution. The results showed that ADSCs stereotactic transplantation improved functional outcomes and reduced cell apoptosis after ICH. Moreover, ADSCs stereotactic transplantation could alleviate brain edema and inflammation and AQP4 protein expression contributed to the alleviation of brain edema. In addition, mitogen‐activated protein kinase (MAPK) pathways, including p38/MAPK pathway and c‐Jun N‐terminal kinase pathway, were involved in AQP4 modulation by ADSCs transplantation in ICH. In conclusion, ADSCs transplantation could alleviate the nervous tissue injury, reduce cell apoptosis, and relieve brain edema in ICH. And the edema regulation effect of ADSCs transplantation is associated with inhibition of inflammation and AQP4 protein expression. Abstract : Adipose‐derived mesenchymal stromal cells (ADSCs) transplantation revealed therapeutic beneﬁts in intracerebral hemorrhage (ICH)‐induced brain edema. Alleviation of brain edema was related to inflammation and AQP4 expression. AQP4 modulation by ADSCs transplantation in ICH was mediated by mitogen‐activated protein kinase (MAPK) pathways.